Kondisi Thermal Masjid Al-Fairus Pekalongan - Taqwim S, M Ainut; Hardiman, Gagoek; Budi, Wahyu Setia (ARSITEKTURA, 2020)
Alfairus Mosque is a mosque that has a design concept that adopts the design of the Nabawi mosque. The building that adopted the design of the Nabawi mosque in Medina has a characteristic high and wide openings on the outer facade with a combination of arch ornaments like most Persian mosque designs. This research focuses on the effect of openings and air movement in space which is a variable used to measure thermal comfort. In the implementation of this research, the existing measurements were carried out when there were no worship activities and measurements when there were worship activities. From the results of the study it was found that the temperature difference was very significant when data collection was in a condition without worship and there were worship activities. In data collection when empty conditions were taken at 10:00 WIB and at the time of worship activities were taken at the time of the Friday prayer service. When empty conditions are obtained the highest effective temperature is 27.80 Â° C, while during worship services the highest effective temperature reaches 32.20 Â° C. And at the highest temperature at each measuring point is the location of the center of the mosque where the location of the measuring point is far from the opening or hole of the mosque. While the lowest temperature is at the location close to the opening of the wall hole where the wind blows from that direction. In this study the lowest temperature was at the north side because at the time of the study the wind blew from the north to the south. Air movement greatly affects the decrease and increase in effective temperature in space, air movement is influenced by openings and wind direction. The higher the air movement the lower the effective temperature.Â